Synthesis and application of novel functionalized nanostructured membranes incorporating N-doped CNT supported metal nanoparticles in water treatment - Phao, Neo (My University, 2013)
In relation to conventional water treatment methods, membrane separation has acquired a great audience due to its wide applicability, reliability, low cost, low energy demands, and ease of use. However, membrane fouling has been identified as the main downsizing factor in the application of this technology. To address this issue, several studies have suggested the use of inorganic additives for enhancement of the membrane antifouling properties. In this study, silver (Ag) decorated nitrogen doped carbon nanotubes (N-CNTs) dispersed into polyethersulphone (PES) membranes for potential use in water treatment. Firstly, N-CNTs were synthesised using the chemical vapour deposition (CVD) method. The black soot was functionalised and characterised using transmission electron microscopy (TEM), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Brunner-Emmett-Teller (BET). The N-CNTs were found to have an average diameter of 15 nm. The functionalised N-CNTs were then decorated with Ag nanoparticles (AgNPs) using the Polyol method. The resultant product was also characterised using TEM, the AgNPs were found to have an average diameter of 6 nm. The N-CNTs and Ag/N-CNTs were then uniformly dispersed into (PES) membranes to form N-CNT/PES and Ag/N-CNT/PES blend membranes, respectively. The membranes were then characterised using several series of techniques including scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle analyser and a cross-flow filtration system. The blend membranes were investigated for any improved properties and tested for their efficiency in removing model pollutants (polyethylene glycol, humic acids, and bacteria) from water. The AFM results revealed a reduction in surface roughness from 23.9 nm for the pristine PES to 12.7 nm in the N-CNT/PES blend membranes. The mechanical stability increased from 3.7 MPa for the pristine PES to 4.4 MPa with a small addition of N-CNTs. Furthermore, the performance studies showed a 46% increase in pure water flux and a 13% increase in rejections for N-CNT blend PES membranes as compared to the pristine PES membrane. Antibacterial studies were also performed where Ag modified N-CNTs were found to inactivate Enterohaemorrhagic E. coli by almost twice the initial concentration in the bacterial suspensions. Finally, Ag/N-CNTs were immersed into PES membranes. The Ag/N-CNTs/PES membranes were then tested for their activity towards the bacteria.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment for the degree of Master of Science in Chemistry. May 2013.
Keywords: Water - Purification.; Nanoparticles.